The health system during neoconservatism in Mendoza: problems and proposals for change between 1932 and 1943 - Hirschegger, Ivana (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2018)
The present investigation intends to make a tour of the Mendoza health system between 1932 and 1943, that is that stage in which the province governed members of the Democratic Party, and which preceded the definitive reorganization of the centralized health system under the orbit of the Ministry of Public Health of the Province, formed in 1950. The fact that the health system during the neoconservative period has not been studied awakens our interest in identifying what were the centralizing signs emerging, the attempts to reorganize the system, and the actions of the State to deal with the different sanitary problems. In this way, it is sought to establish some connections with respect to subsequent governments and to know mainly those initiatives that, originating in the neoconservative governments, were inherited by the Peronists.